Correction to: Double Layer Composite Electrode Strategy for Efficient Perovskite Solar Cells with Excellent Reverse-Bias Stability - Jiang, Chaofan; Zhou, Junjie; Li, Hang; Tan, Liguo; Li, Minghao; Tress, Wolfgang; Ding, Liming; Grätzel, Michael; Yi, Chenyi (Nano-Micro Letters, 2023)
Perovskite solar cells (PSCs) have become the representatives of next generation of photovoltaics; nevertheless, their stability is insufficient for large scale deployment, particularly the reverse bias stability. Here, we propose a transparent conducting oxide (TCO) and low-cost metal composite electrode to improve the stability of PSCs without sacrificing the efficiency. The TCO can block ion migrations and chemical reactions between the metal and perovskite, while the metal greatly enhances the conductivity of the composite electrode. As a result, composite electrode-PSCs achieved a power conversion efficiency (PCE) of 23.7% (certified 23.2%) and exhibited excellent stability, maintaining 95% of the initial PCE when applying a reverse bias of 4.0 V for 60 s and over 92% of the initial PCE after 1000 h continuous light soaking. This composite electrode strategy can be extended to different combinations of TCOs and metals. It opens a new avenue for improving the stability of PSCs. Highlights: 1 A composite electrode strategy to fabricate the perovskite solar cells (PSCs) with excellent comprehensive stabilities, particularly reverse-bias stability. 2 A record efficiency of 23.7% (certified 23.2%) for n-i-p PSCs using Cu as the electrode. 3 The strategy can be extended to the combinations of different transparent conducting oxides and low-cost metals.